Answer:
The answer is "
"
Step-by-step explanation:
Let the given value is: ![\frac{x-6}{x^2+x-6}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-6%7D%7Bx%5E2%2Bx-6%7D)
![\to \frac{x-6}{x^2+x-6}=\frac{x-6}{x^2+(3-2)x-6}\\\\](https://tex.z-dn.net/?f=%5Cto%20%5Cfrac%7Bx-6%7D%7Bx%5E2%2Bx-6%7D%3D%5Cfrac%7Bx-6%7D%7Bx%5E2%2B%283-2%29x-6%7D%5C%5C%5C%5C)
![=\frac{x-6}{x^2+(3-2)x-6}\\\\ =\frac{x-6}{x^2+3x-2x-6}\\\\ =\frac{x-6}{x(x+3)-2(x+3)}\\\\ =\frac{x-6}{(x+3)(x-2)}\\\\=\frac{A}{(x-2)} + \frac{B}{(x+3)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bx-6%7D%7Bx%5E2%2B%283-2%29x-6%7D%5C%5C%5C%5C%20%3D%5Cfrac%7Bx-6%7D%7Bx%5E2%2B3x-2x-6%7D%5C%5C%5C%5C%20%3D%5Cfrac%7Bx-6%7D%7Bx%28x%2B3%29-2%28x%2B3%29%7D%5C%5C%5C%5C%20%3D%5Cfrac%7Bx-6%7D%7B%28x%2B3%29%28x-2%29%7D%5C%5C%5C%5C%3D%5Cfrac%7BA%7D%7B%28x-2%29%7D%20%2B%20%5Cfrac%7BB%7D%7B%28x%2B3%29%7D)
Answer:
Adding 3
Step-by-step explanation:
-3 + 3 = 0
0 + 3 = 3
3 +3 = 6
6 + 3 = 9
Answer:
8 blocks away
Step-by-step explanation:
You just add
Multiply each side of the equation by 4. Then see whether the equation makes sense.
Answer:
(3, - 1)
Step-by-step explanation:
5x - 4y = -11
2x + 3y = -9
Multiply the top equation by 2 and the bottom equation by - 5 to cancel out the x's.
10x - 8y = - 22
- 10x - 15y = 45
Cancel out x's.
-8y = - 22
- 15y = 45
Add like terms.
- 23y = 23
Can't have a negative variable to flip them.
-23 = 23y
Divide.
y = - 1
Input y into one of the equations and solve for x.
2x + 3(-1) = -9
Simplify.
2x -3 = -9
Cancel out -3 by adding 3.
2x = -6
Divide.
x - -3